Analisis dampak kebijakan pengembangan lahan gambut 1 juta Ha di Kalimantan Tengah - LIHARFIN SK, LIHARFIN SK (Universitas Gadjah Mada, 1998)
A studi on issue related to a public policy should consider at least a number of substantive analysis, some of which are formulation of policies, implementation, evaluation as well as an analysis of the impacts policy. The latter mentioned connotes “assessment” (judgement or estimation) and the same consideration may be applied to make an evaluation of the implemented policy. It i s within this analytical h e wo& that the thesis “Assessment of the Impacts of a Policy on the GWivation of i Million Hectares of Peat Soil ( h d ) in Central Kdimantan ‘* is to be understood The above mentioned policy is Presidential Decree Number 82 of 1995 concerning (opening) of new ~ c u l h r r a l lands, construction of supporting hilities and settlement of h e r s (transmigrants)in a stretch of and irrigation system. The goal to be acheived is the fulfillment of programmers have been set up to acheive the goal, starting fiom January 1996 and to be comlpleted in 2002. The research w s carried out one and a m y e a r s after the policy was put into efect a The method or approach adopted here is the formative evaluation or, better known as assessment, i.e. examining the impacts of implementation, and at the same time mapping out or predicting permanent impacts. It i s hoped that the same method will help measure the success of progt-atnme (surmnative evaluation) at the completion of the whole implementation. Operationally : 1. The research variables consist of Presidential Decree Number 82 o f 1995 as an independent variable (policy variable) and the phisical, economic, social as well as demography, institutional impacts as independent variable or outcomes. The sources and types of data are the Regional Government of Central Kalkmntan 2. (province), the Local Government (regency), the project location (henceforth PLO) and related agencies, project implementer, the community affected by the impacts, and other sources that can contribute ideas on posible impacts. The required data are secondary data in the fiom of features of the research location, policy variables as well as results of previous researchh addition, there is a need for data of a survey on the perception of the proaject implementer, government officials and other parties concerned; 3 . The tecnique of data collection consists of a documentary study to obtaib secondary data and a survey through interviews and a questionaire to elicit idormation and discover the respondens attitudes and perception, as well as direct observation in the project location; 4. Data analysis and interpetation are made qualitatively using table or matrices in oder to obtain both positive and negative significance according to the 7 (seven) criteria of impact determinants. Results of the analysis an social impacts based on the chosen variables after the evaluation indicate ther are 24 kinds of impact consisting of 2 insignificant negath impacts (-TP), significant negative impacts (-P) and 14 significant positive impacts (+P). Although 8 the results have indicated that there are more positive impacts than negative ones, .and bearing in mind that the analysis is loaded with assessment and that PLG is still at the implementation stage until the year 2002, the composition and intensity that the impact are subject to changes. However, it is hope that the results of this research can contibute ideas as formulated in the recommendation for the management of impact, particulary social impact.